Service Quality and Customer Satisfaction with Commercial Banks in the Nawalpur District (Madhyabindu Journal, 2024)
The degree to which a consumer feels that a person, business, or organization has successfully delivered a good or service that satisfies their demands in the circumstances in which they are aware of utilizing the good or service is known as customer satisfaction. The specific objectives of this study are to assess various aspects of service quality provided by commercial banks in Nawalpur, to determine and compare the extent of customers’ satisfaction with the quality of banking services based on different constituent factors, to identify the bank-related factors which influence the service quality. This study is based on primary sources of data. The primary data analysis used different statistical tools like Cronbach's alpha, mean, correlation, and regression analysis. The major conclusion of this is that the level of quality service delivery and its effect on customer satisfaction at commercial banks in Nawalpur. Generally, the responses to service quality dimensions used to measure the performance of the banking services provided by commercial banks in Nawalpur are relatively high.